Tea, coffee and prostate cancer: A case-control study in Vietnam - Hoang, Dong Van (Curtin University, 2016)
A case-control study including 216 prostate cancer (PCa) patients and 399 controls was conducted in Southern Vietnam between 2013 and 2015 to investigate the associations between tea and coffee consumption and PCa risk. Habitual tea, but not coffee, consumption was significantly associated with reduced PCa risk in Vietnamese men. The inverse association was more apparent for high grade than lower grade PCa. These findings suggest a protective effect of tea consumption against PCa development.